Effects of Athermal Shortwave Diathermy Treatment on Somatosensory Evoked Potentials and Motor Evoked Potentials in Rats With Spinal Cord Injury. Issue 13 (1st July 2019) - Xie, Caizhong; Li, Xiangzhe; Fang, Lu; Wang, Tong
Abstract : Study Design: A study on shortwave diathermy (SWD) versus no treatment following induced spinal cord injury (SCI) in rats. Objective: To investigate the effects of athermal SWD treatment on somatosensory evoked potentials (SEPs) and motor evoked potentials (MEPs) and hindlimb movements in rats with SCI. Summary of Background Data: SWD has been proven to improve vascular circulation and reduce inflammation. However, there have been few studies on neuroprotective effect of SWD on SCI. Methods: Twenty-four female Sprague–Dawley (SD) rats were randomly divided into four groups: sham, SCI, SWD, and intact groups. The SCI model was established using the modified Allen weight-drop method. The SWD group received 15 sessions of athermal SWD treatment over a 3-week period of time at 24 hours after SCI. While the sham group and SCI group received no treatment after surgery. Hindlimb movements were evaluated by the Basso, Beattie, and Bresnahan (BBB) scale before surgery, and on days 1, 7, 14, and 21 after the surgery, respectively. The SEP and MEP measurements were simultaneously performed to detect the responses of neural conduction. Results: The week-by-week BBB scores showed a gradual improvement in the rats of both SCI and SWD groups from the first week to the end of the study; however, the BBB scores of the SWD group were higher than those of the SCI group over the course of 3 weeks. Data from the SEP and MEP measurements showed a significant improvement in the SWD group compared with the SCI group at each time point of observation, with a more prominent increase of amplitude and a more evident reduction of latency. There was a linear correlation between the BBB scores and the latency and amplitude of SEPs or MEPs. Conclusion: Athermal SWD treatment might facilitate the recovery of locomotor function and exert neuroprotective effect on the SCI. Level of Evidence: N/A Abstract : We have explored the effects of athermal shortwave diathermy (SWD) in spinal cord injury (SCI). Sprague–Dawley rats received athermal SWD treatment at 24 hours after SCI. The Basso, Beattie, and Bresnahan scales and somatosensory evoked potentials and motor evoked potentials were used to measure changes of neurological function. Our results showed that athermal SWD treatment exerts neuroprotective effect in SCI.